Pediatric urological surgery readiness condition (PedsUROCON) - Ferreira, Roseanne; Keefe, Daniel; Wang , Yuding; McGrath, Melissa; Koyle, Martin A.; Siemens, D. Robert; Braga, Luis H. (Canadian Urological Association Journal, 2020)
NA